An Observation of Blue Duffer Discophora necho (Rhopalocera: Nymphalidae) Fed on Carrion of Blue Coral Snake Calliophis bivirgatus (Serpentes: Elapidae) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Studies on the exploration of different food resources by adult butterflies in Indonesia have been relatively little attention. On 24 September 2022, a Blue Duffer Discophora nechohas been observed feeding on carrion of snake (Blue Coral Snake Calliophis bivirgatus) in the remaining secondary forest in Batu Gane Village, South Sumatra Province. This observation is a very interesting record, due to the lacking information on different food sources by adult butterflies in Sumatra, particularly when a butterfly feeding on the carrion of a snake.